The Role of Scaffolding in Early Literacy Development among First-Grade Students in Cambodian Primary Schools - Linna Nin; Da BOU; Borey Chhen; Rorthmony Norm; Smiror Vann (English Lecturers and Teachers Association (ELTA), 2026)
Early-grade students in elementary schools must master consonants and vowels to develop accurate reading and spelling skills. This study investigates the effectiveness of word writing among Cambodian first graders with three main objectives: (1) to assess the efficacy of writing consonants and vowels, (2) to examine the relationship between orthographic ability and word-writing skills, and (3) to evaluate teacher motivation for facilitating students' writing practice. A quasi-experimental (pretest-posttest) design was employed, involving observations of 41 first-grade students. Findings indicate a statistically significant improvement in the mean score from M = 5.65 (SD = 2.80) to 8.45 (SD = 2.77), a t-test (t = 5.318***; P-value = 0.000), and a coefficient (r = 0.63) shows that students proficient in writing consonants and vowels demonstrate improved spelling abilities and strength positively relation of their writing words. Additionally, students demonstrated enjoyment, active participation, and cooperation during classroom activities, and showed increased confidence in writing on the boards. Further research should investigate the impact of this approach on writing skills, including the construction of longer words, phrases, and sentences, as well as reading comprehension, among second- and third-graders, thereby testing the effectiveness of scaffolding across various educational contexts. Keywords: consonants, primary education, scaffolding strategy, vowels, word writing